Precision Care Pada Penderita Penyakit Kronis Dan Penyadang Disabilitas Melalui Peran Care Giver dan Kader Surabaya Hebat di Wilayah Puskesmas Gading Surabaya - Winata, Septian Galuh; Priyantini, Diah; Asri, Asri; Rofiqi, Erfan; Yunita Prabawati, Chlara (Jurnal Keperawatan Muhammadiyah, 2024)
The results of this study indicate that there is an effect of audio-visual on increasing the ability to recognize pregnancy danger signs as evidenced by the results obtained P value = 0.000 then p value <0.05. The use of audio visual signs of pregnancy danger can improve memory through stimulation of the senses of hearing and sight so that the message obtained is more optimal. The conclusion is that there is an influence of audio visuals on increasing the ability to recognize pregnancy danger signs. The problem faced by health services in the community is the lack of access to see the needs in depth for people with chronic diseases and people with disabilities to improve health and quality of life. This descriptive qualitative study aims to explore the application of health services in the management of chronic diseases and people with disabilities and their impact on quality of life. Precision Care offers a highly personalized and tailored approach to patient care, with the goal of improving their satisfaction and quality of life. The study participants were caregivers, Surabaya Hebat cadres and health service providers. A total of 20 participants were recruited using non-probability sampling with purposive sampling techniques. The findings showed that Precision Care provided more personalized and effective care, increased independence, and reduced disease symptoms. However, its implementation faces several challenges such as lack of training, inadequate infrastructure, and the need for policy support from the government. This study also highlights the importance of technology and effective communication in supporting Precision Care. Support from families and caregivers and their involvement in the care process are also considered important for the success of Precision Care. In conclusion, although Precision Care offers many benefits, its successful implementation is highly dependent on adequate policy support, infrastructure, training, and technology.